Opa1 Prevents Apoptosis and Cisplatin-Induced Ototoxicity in Murine Cochleae - Dong, Tingting; Zhang, Xuejie; Liu, Yiqing; Xu, Shan; Chang, Haishuang; Chen, Fengqiu; Pan, Lulu; Hu, Shaoru; Wang, Min; Lu, Min (Frontiers in Cell and Developmental Biology, 2021)
Optic atrophy1 (OPA1) is crucial for inner mitochondrial membrane (IMM) fusion and essential for maintaining crista structure and mitochondrial morphology. Optic atrophy and hearing impairment are the most prevalent clinical features associated with mutations in the OPA1 gene, but the function of OPA1 in hearing is still unknown. In this study, we examined the ability of Opa1 to protect against cisplatin-induced cochlear cell death in vitro and in vivo. Our results revealed that knockdown of Opa1 affects mitochondrial function in HEI-OC1 and Neuro 2a cells, as evidenced by an elevated reactive oxygen species (ROS) level and reduced mitochondrial membrane potential. The dysfunctional mitochondria release cytochrome c, which triggers apoptosis. Opa1 expression was found to be significantly reduced after cell exposed to cisplatin in HEI-OC1 and Neuro 2a cells. Loss of Opa1 aggravated the apoptosis and mitochondrial dysfunction induced by cisplatin treatment, whereas overexpression of Opa1 alleviated cisplatin-induced cochlear cell death in vitro and in explant. Our results demonstrate that overexpression of Opa1 prevented cisplatin-induced ototoxicity, suggesting that Opa1 may play a vital role in ototoxicity and/or mitochondria-associated cochlear damage.